Diffraction and interference: measurement of the wavelength of the visible light spectrum. (Research, Society and Development, 2020)
The work aims to establish and improve the teaching and learning processes, through an experimental activity carried out in the Physics laboratory, in the Physics degree course at IFMA-Campus São João dos Patos. Aiming to know and understand the diffraction and interference phenomena, with the main objective to show and calculate the average wavelength of the visible spectrum (380-740nm) through a diffraction network, thus being able to enrich the studied concepts, through a reflective analysis of Young's experiment, stimulating the creation of new theoreticians, serving to show students the behavior of light as a wave, knowing that diffraction is the deviation from a straight path, which when passing through an orifice or being obstructed by a obstacle suffers an enlargement or bending, spreading to different regions, acting as if it were new sources, causing the scattering of light. In this way, encouraging the teacher to use and create procedural methodologies, allowing the student an environment conducive to participate and develop their intellectual skills and abilities, thus being able to associate theory with practice, validating concepts and equations to calculate the length of wave, obtaining as a result the verification of the effectiveness of the calculation from the symmetry of the luminous intensities in relation to the central one, being able to compare the calculated values of the radiations with those of the literature. Thus, through practices, they can instigate, establish and awaken students' desire for knowledge through science.